Prepectoral Implant-Based Breast Reconstruction Using Meshed ADM. Issue 2 (May 2021) - Fin, Alessandra; De Biasio, Fabrizio; Mura, Sebastiano; Massarut, Samuele; Zaccaria, Giovanna; Parodi, Pier Camillo
Prepectoral prosthetic breast reconstruction has been widely reassessed in recent years and is taking on an increasingly important role in the field of immediate breast reconstruction. We report here a case series of 32 patients who underwent nipple-sparing mastectomy for breast carcinoma and prepectoral breast reconstruction involving an acellular dermal matrix (ADM) treated by means of a skin-graft mesher in our hospital from January 2015 to March 2016. The indications for this type of reconstruction were body mass index (BMI) less than 30 kg/m 2 ; no history of radiotherapy; no active smokers; moderate grade breast; and good viability of mastectomy flap: normal skin colour, active bleeding at the fresh cut edges, and thicker than 1 cm mastectomy flaps; the viability of lower thicknesses was ascertained by the fluorescent dye indocyanine green xenon-based imaging technology (4 patients). The mean age of the patients was 56.4 years (range: 39-77 years). Their mean BMI was 27.4 kg/m 2 . Until the end of follow-up (mean: 17 months), major complications requiring reoperation occurred in 9% of patients and minor complications in 22% of patients. The mean of the 3 pain visual analogue scale scores taken in the first 24 hours after surgery was 1.8. Mean duration of hospital stay has been 2.2 days. Our complication rate was similar to those reported in other studies on prepectoral breast reconstruction featuring total ADM coverage of the implant.